Topical Breastmilk: Nursing Care of Newborn Umbilical Cord Model - Kasiati Kasiati; Budi Santoso; Esti Yunitasari; Nursalam Nursalam (Jurnal Ners, 2013)
Introduction: Omphalitis and umbilical cord separation time contributing to the number of morbidity and mortality in infants. There are various ways of cord care, but there was no significant difference in prevent of infection and cord separation time. Breast milk contains anti-infective and antiinflammatory factors that can be used for cord care. WHO recommends to develop it. The purpose of this study was to analyze the effect of topical breastmilk model on the incidence of omphalitis and separation time of the umbilical cord to the newborn.Methods: The study design was a quasy experimental. The subjects of this study were 30 newborns obtained by consecutive sampling in Rumah Sakit Ibu dan Anak Kendangsari Surabaya May–June 2012. The samples were divided into 2 groups (topical breastmilk and open dry treatment), each group consists of 15 newborns. Data were analyzed using chi-square and independent t-test with a signifi cance level ofα≤0.05.Results: There was no difference in the incidence of omphalitis in the use of topical breastmilk model compared to open dry treatment (p=0.33). However, there are significant differences in the average of cord separation time between topical breastmilk model and open dry treatment (p=0.020).Conclusion: Model of cord care with topical breastmilk lowers the risk of omphalitis and accelerate the cord separation time compared to open dry treatment. Using breastmilk as cord care are safe, effective and efficient.